EVALUATION OF PUMPKIN PEEL POWDER (Cucurbita moschata durch) DIETARY SUPPLEMENTATION ON GROWTH AND COLOR IMPROVEMENT IN LEMON FISH (Labidochromis caeruleus) - Yuniar Cindi Aulia; Shobrina Silmi Qori Tartila; Eric Armando (JURNAL AKUAKULTURA, 2025)
This study aimed to determine the supplementation of yellow pumpkin peel powder on the coloration of lemon fish. The powder lemon fish with an average length of 3 cm and a weight of 0.83 g as many as 240 fish. This study used a completely randomized design (CRD) consisting of four treatments and four replicates, namely P1 (0 g/100 g feed), P2 (5 g/100 g feed), P3 (10 g/100 g feed), and P4 (15 g/100 g feed). The aquariums used were 50x30x30 cm in size, with 16 aquariums and 15 fish per aquarium. The fish were reared for 30 days and fed based on fish biomass. The parameters observed were growth performance (absolute weight, absolute length, and survival), water quality, feed nutrient levels, and increased color intensity. Data on growth performance and increased color intensity were analyzed using a one-way analysis of variance (one-way ANOVA) to determine the real difference between each treatment and followed by the Duncan multiple distance test (DMRT) with a 95% confidence interval (p<0.05). Water quality data and feed nutrient levels were analyzed descriptively. The results of the study showed that dietary supplementation with yellow pumpkin peel powder did not affect the growth performance of lemon fish, but it did affect the coloration of lemon fish. The best treatment for increasing the color of lemon fish was P4, with a color increase value of 31.5%.